Emerging Trends and Challenges in English Literature - Kiran; Kumar, Narendra (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
In this paper, we have discussed emerging trends and challenges in English Literature. Firstly, we have discussed what literature is, its different ages and what kind of literature was written in those times. There are many trends which have emerged already like micro fiction and flash fiction, six word novels, twitter fiction, graphic novels. On one side it made writing easier for people but on the other side it degraded the language badly, grammar has lost its value and research has become history. We are facing it since the advent of the Internet, where everything is available online and no one wants to pause and read lengthy novels where shorter versions are available online. Everyone has become impatient and has less attention span especially the newer generation and this is the biggest challenge of writers to hold the attention. We are living in an abundance of concepts, signs and words. Change that we are facing in today’s times; we avoid this because it is uncertain and unknown.